2019
DOI: 10.1177/1934578x1901400133
|View full text |Cite
|
Sign up to set email alerts
|

Arugosins O-Q, New Fungal Metabolites from the Fungus Xylariaceae sp. Isolated from Leaves of Lansium domesticum (Meliaceae)

Abstract: A fungal endophyte which was identified as a hitherto undescribed member of the family Xylariaceae by sequencing of the ITS region was isolated from fresh and healthy leaves of Lansium domesticum collected on tropical peatland of West Kalimantan, Indonesia. Chromatographic separation of the ethyl acetate extract of the fungus resulted in the isolation of three new arugosin type metabolites, including arugosins O (1), P (2), and Q (3). The structures were determined by analysis of 1D and 2D NMR spectra and HRMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, new dibenzoxepin derivatives named arugosins O (35) to Q were reported from an unidentified Xylariaceae sp. [54]. No effects were observed in assays evaluating antibacterial or cytotoxic activities.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, new dibenzoxepin derivatives named arugosins O (35) to Q were reported from an unidentified Xylariaceae sp. [54]. No effects were observed in assays evaluating antibacterial or cytotoxic activities.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 98%
“…Preliminary structure-activity relationships of cytochalasans were derived and it was shown that actin-disrupting effects are reversible in some cytochalasans, while being permanent in others. However, the work also described two unprecedented cytochalasans from Hypoxylon fragiforme, named fragiformins C and D (54). While fragiformin C attained incomplete actin disruption at 5 µg/mL and was partially reversible, fragiformin D (54) was highly active, yielding complete disruption at 1 µg/mL without reversibility [18].…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 99%
“…C. macrophyllus [ 21 ], X. granatum [ 22 ], M. azedarach [ 23 ], T. sinensis [ 24 ], C. tagal [ 25 ], A. indica [ 26 ], T. monadelpha [ 27 ], T. longipes [ 28 ], D. binectariferum [ 29 ], and L. domesticum [ 30 ] are members of the Meliaceae family with endophytic fungi that create secondary metabolites. The 276 secondary metabolites isolated are composed of 82 terpenoids, 12 polyketides, nine lactones, six pyrones, one quinone, 15 anthraquinones, nine xanthones, 10 isocoumarines, 13 resorcylic acid lactones, 25 cytochalasins, 18 aromatics, one ester, seven quinols, 59 alkaloids, one nitro compound, and eight fatty acids and sugars ( Figure 1 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64...…”
Section: Phytochemistrymentioning
confidence: 99%
“…fungi found in A. indica root [ 53 ]. New anthraquinones such as emodin (1,6,8-trihydroxy-3-methylanthra-quinone) ( 111 ), citreorosein (1,6,8-trihydroxy-3-methylanthraquinone) ( 112 ), and janthinone ( 113 ) were obtained from P. janthinellum , isolated as an endophytic fungus from M. azedarach fruits grown on the ground for 20 days and autoclaved white corn [ 51 , 54 ].…”
Section: Phytochemistrymentioning
confidence: 99%
“…In addition, the 2-benzoxepine core is found in many natural products, namely, Dioscorealide B, a pharmacologically active naphthofuranoxepin isolated from rhizome of Dioscorea membranacea ; Linoxepin, a lignan-containing benzonaphtho­[1,8- bc ]­oxepine moiety isolated from Linum perenne L. (Linaceae); Alterlactone, a mycotoxin produced by Alternaria sp . ; fungal metabolites Arugosins; Cladoacetals A and B isolated from solid-substrate fermentation cultures of fungicolous isolate (NRRL 29097); and Xylarinol A and 8-Chloroxylarinol A isolated from the fruiting bodies of the Xylaria polymorpha and from the extract of the grain-based culture of Malbranchea flavorosea , respectively (Figure ).…”
Section: Introductionmentioning
confidence: 99%